2015
DOI: 10.18632/oncotarget.6534
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA-based prediction model for lymph node metastasis in hepatocellular carcinoma

Abstract: We developed an efficient microRNA (miRNA) model that could predict the risk of lymph node metastasis (LNM) in hepatocellular carcinoma (HCC). We first evaluated a training cohort of 192 HCC patients after hepatectomy and found five LNM associated predictive factors: vascular invasion, Barcelona Clinic Liver Cancer stage, miR-145, miR-31, and miR-92a. The five statistically independent factors were used to develop a predictive model. The predictive value of the miRNA-based model was confirmed in a validation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…miR-145 has also been suggested as one of the predictive factors for the early prediction of lymph node metastasis in patients with hepatocellular carcinoma (6). Although previous studies report miR-145 is one of the most down-regulated miRNAs in both superficial Ta-T1 bladder tumors and invasive T2–T4 tumors with no significant difference between these two stages of human BC (3942), the correlation of miR-145 expression with BC with lymph node metastatic status has never been explored.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-145 has also been suggested as one of the predictive factors for the early prediction of lymph node metastasis in patients with hepatocellular carcinoma (6). Although previous studies report miR-145 is one of the most down-regulated miRNAs in both superficial Ta-T1 bladder tumors and invasive T2–T4 tumors with no significant difference between these two stages of human BC (3942), the correlation of miR-145 expression with BC with lymph node metastatic status has never been explored.…”
Section: Disscussionmentioning
confidence: 99%
“…However, it has recently been found that tumor-specific deletion of miR-145 in an autochthonous mouse model of lung adenocarcinoma did not affect tumor development, and that stromal expression of miR-145 promotes neoangiogenesis in lung cancers (5), thus arguing against the delivery of this miRNA as an agent in cancer therapeutics. Moreover, miR-145 displays dramatic up-regulation in hepatocellular carcinoma and colorectal cancers with lymph node metastasis in comparison to those without lymph node metastasis (6, 7), suggesting that miR-145 may promote lymph node metastasis of cancer, or it may even play an oncogene role in metastatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evaluation results of AUS may vary between examiners, and the overall accuracy of AUS remains controversial, especially in low‐burden lymph node disease. A miRNA‐based prediction model for lymph node metastasis in hepatocellular carcinoma has been developed, which can effectively and accurately classify patients into groups with low risk or high risk of developing lymph node metastasis . Our study here first evaluated the usefulness of miRNAs signature as an effective molecular approach for the preoperative diagnosis of ALN metastases in EIBC.…”
Section: Discussionmentioning
confidence: 99%
“…A miRNA-based prediction model for lymph node metastasis in hepatocellular carcinoma has been developed, which can effectively and accurately classify patients into groups with low risk or high risk of developing lymph node metastasis. 28 Our study here first evaluated the usefulness of miRNAs signature as an effective molecular approach for the preoperative diagnosis of ALN metastases in EIBC. The results suggest that the evaluation of nine miRNAs expression could be an important tool for the management of EIBC patients, The y axis displays the net benefit, which was calculated by minusing the proportion of false-positive patients from the proportion of true positive patients, weighting by the relative harm of giving up treatment compared to the negative effects by unnecessary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Liver biopsy was also reported to increase the risks for distant metastasis and reduce survival. 19 Thus, a noninvasive method which can predict the probability of liver metastasis of patients with PDAC is needed. In this study, we have developed and validated the predictive nomograms using the SEER dataset, which demonstrated significant discrimination and calibration to provide evidence-based and individualized estimation for the probabilities of liver metastasis in patients with PDAC.…”
Section: Discussionmentioning
confidence: 99%